Flipped Classroom for Teaching English at Senior High Schools in Banjarmasin - Elvina Arapah Arapah (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2023)
In an online or a hybrid English flipped classroom, the traditional teaching and learning processes instruction is changed. The English lesson does not start with the face-to-face meeting in which the teacher will explain the materials, but the students are supposed to start by themselves studying the learning materials, which are shared by the teachers virtually before the classroom start. The materials can be utilized from many different digital learning platforms such as websites, YouTube channels, and presentation, pdf files and so forth. This research is aimed to investigate: 1) what flipped materials are utilized by the Senior High School English teachers for English reading assessment during the Covid-19 Pandemics; and 2) how the Senior High School English teachers in Banjarmasin utilize the flipped materials for the English reading assessment during the Covid-19 Pandemics. This qualitative study involves Senior High School English teachers, who teach at either state or private schools in Banjarmasin, as the subjects. The selection of those teachers depends on their willingness to participate in the interview. In short, the teachers are familiar enough with some Learning Management Systems (LMS) as the software application or web-based technology used to upload the materials. Teachers also provided some materials before attending class, and the students are required to do a preparatory study prior to face-to-face meeting. For the in-classroom session, the teachers review the materials and later use them for the assessment of reading.